Hotspot detection method for photovoltaic system: A review - Tan, Li Ven; M. S., Jadin (2020)
To maintain the long-term reliability of photovoltaic (PV) modules while maximizing the power output, possible faults in the PV modules need to be diagnosed at an early stage. One of the problems that arises in PV system is the formation of hotspot. Numerous hotspot detection methods have been presented over the years to address this particular issue. This paper presents a review of existing hotspot detection methods for PV system. Several methods are discussed and the future possible works are recommends in this study.